Factors influence bond price in Malaysia market / Nur Diana Ramlan - Ramlan, Nur Diana (2011)
In late 1990s corporate bond plays a significant role in stabilizing financial systems and economic growth. It emerged as an alternative option for acquiring funds from large number of publics at the market rate (Nozue, 2007). Bonds consist of paper having a stated amount of coupon rate, maturity time and face value. It is categorized as debt because of its interest feature and superior nature at the time of liquation. The main purpose of this study is to determine the factors that affect the bond price in Malaysia bond market. This study, suggest that the factors that influence bond price are inflation rate, interest rate and yield to maturity (bond yield) of the bond. The study shown that, there are significant relationship between the factors and bond price. The bond price has positive relationship with the inflation and inverse relationships with interest rate and bond yield. Interest rates are found to be the most factors that influence the bond price volatility.